Creating sustainable city by enhancing social capital. (March 2018) - Affandi, R A; Mursitama, T N
Abstract: Scholars have been discussing social capital since the last two decades. They analyzed from various perspectives such as sociology, education, political participation, strengthening democratic values and economic empowerment of the society. However, study related to the implementation that benefits directly to the society is needed. This study examines how to create a sustainable city by enhancing social capital from both macro and micro analyses. This combination of analysis offers deeper understanding both from decision makers at city level and individuals, groups and society. We will conduct qualitative approach mainly by interviews and direct observation to collect the data. also, we also analyze publicly available data. Finally, this study contributes to new understanding in creating a sustainable city, not only about the environment and physical aspects, but also about ensuring political economic, democratic values, and social welfare.